DESKRIPSI PELAKSANAAN PEMBELAJARAN SECARA DARING PADA MASA PANDEMI COVID-19 DI SD KHATOLIK MARIA FERRARI - Maria Herliyani Dua Bunga; Bergita Nona Timur; Frederiksen Novenrius Sini Timba (Universitas Islam Nahdlatul Ulama Jepara, 2022)
The study aims to implement bold thematic learning (online) during the CoronaVirus Diseases 2019(Covid -19) pandemic at the Maria Ferrari SDK. This study used qualitative research methods. The results show that thematic learning boldly uses applications: Microsoft Office Word, Microsoft Office PowerPoint, WhatsApp, Google Forms, Format Factory, Fast Tone Capture, VideoScribe, and Youtube. The teacher provides learning materials and videos for students to study at home so that students carry out learning boldly through learning applications. The teacher also provides quiz questions, tests, and exams so that students can work on these questions boldly. Based on the results of the study, it can be seen that the thematic learning implementation process is boldly carried out by utilizing applications to design teaching materials and learning videos for students as well as presenting questions so that the bold learning process can run effectively and efficiently.